(NiMQ SU]ESTWITELXNOE W RUSSKOJ RAZGOWORNOJ RE^I (B:s (NfUNKCIONALXNYJ ASPEKT (B/s - (NkRASILXNIKOWA(B, (NeLENA wASILXEWNAs; (NgRIGORXEW(B, (Nw(B. (Np(B.s ((NmOSKWA (B:s (NnAUKA (B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 118-124s
Keywords: (NgRAMMATIKAs; (NiMQ SU]ESTWITELXNOE W RUSSKOM QZYKEs; (NkOMMUNIKATIWNAQ FUNKCIQs; (NrAZGOWORNAQ RE^Xs